Phenobarbitone in previously untreated epilepsy. Issue 4 (April 1980) - Feely, M; O'Callagan, M; Duggan, B; Callaghan, N
Abstract : In a prospective study we used phenobarbitone to treat 13 new patients with epilepsy (eight adults and five children). Full seizure control was achieved in 11 patients and poor compliance was documented in one of the remaining two patients (in both of whom seizures were reduced by over 50%). Doses sufficient to give mean steady state plasma levels of more than 43 mumol/l (10 microgram/ml) appeared to be associated with better seizure control than lower doses. No serious side effects were observed.